The relationship between premature birth and caregiver first concern in toddlers with autism spectrum disorder: A brief report. Issue 4 (19th May 2017) - Goldin, Rachel L.; Matson, Johnny L.; Matheis, Maya; Jang, Jina
ABSTRACT: The current study examines the relationship between premature birth and the age at which caregivers first become concerned with their child's development in a sample of 84 toddlers with autism spectrum disorder (ASD). The participants were split into two groups: those born prematurely and those born full term. The results indicate that the age of caregiver first concern is significantly younger for those born prematurely than those born full term. The average age caregivers reported first becoming concerned about their child's development was around 7 months for participants born prematurely and around 13 months for participants born full term. Possible explanations for the results and their implications are discussed.